Improving Mathematical Critical Thinking Skill through STEM-PjBL: A Systematic Literature Review - Setyawati, Rina Dwi; Pramasdyahsari, Agnita Siska; Astutik, Iin Dwi; Nusuki, Ukima; Aini, Sindi Nur; Arum, Julia Puspita; Widodo, Wahyu; Salmah, Ummy; Zuliah , Nafiatuz (Universitas Terbuka, 2022)
Critical thinking is one of the important competencies in the twenty-first century that should be acquired. Therefore, there is a need to facilitate the students with the teaching approach and learning model that could improve this skill. One of the learning approaches that provide the students with the opportunity to think creatively is STEM-PjBL. Therefore, the purpose of the study is to describe the application of STEM-PjBL able to increase the critical thinking skills of the student. The SLR or Systematic Literature Review method was chosen to present a comprehensive and balanced summary of primary research results. The literature review was conducted through Google Scholar, Crossref, and Scopus. From 100 works of literature, 15 articles showed that PjBL STEM learning was able to improve critical thinking skills. This study examined 15 articles that were analyzed based on research methods, and the findings revealed that the application of STEM-PjBL could enhance the critical thinking skills of the student with the literature review method. Based on the existing data collection, it is analyzed through case studies that are the subject of discussion. The findings of the study revealed that: 1) the use of STEM-PjBL had a positive and significant impact on the critical thinking skills of students in each educational unit, including primary school, secondary schools, and high school; 2) the use of STEM-PjBL can help students improve their mathematical critical thinking skills; 3)Ã‚Â interpretation, analysis, inference, evaluation, explanation, and self-regulation are among the indicators recommended for use as a reference for students' mathematical critical thinking skills.